Genetic Diagnostic Elucidation of a Patient With Multiorgan Granulomas, Facial Peculiarities, and Psychomotor Retardation - Soukup, Daniel; Kuechler, Alma; Roesler, Joachim; Pichlmaier, Leopold; Eckerland, Maximillian; Olivier, Margarete; Stehling, Florian (Frontiers in Genetics, 2018)
We report the case of a 19 year old patient who presented with a perplexing variety of symptoms which included remarkable facial features, intellectual disability, granulomatous upper lip swelling (previously diagnosed as Melkerson Rosenthal syndrome), Crohn´s-like disease, non-productive cough and a granulomatous mass localised in the left lung. Chronic granulomatous disease (CGD) was diagnosed using dihydrorhodamine 123 assay that showed low levels of phagocytic NADPH-oxidase. DNA sequencing revealed a heterozygous mutation in the NCF-1 gene on chromosome 7. As remarkable facial features and psychomotor retardation are not associated with CGD, a more detailed genetic work-up using fluorescence in situ hybridisation was performed. A microdeletion in 7q11.23 on one allele indicated Williams-Beuren syndrome (WBS). The NCF-1 gene and its two pseudogenes are part of a highly repetitive region within 7q11.23 and are prone to recombination events and deletions. Such deletions can involve both the WBS critical region and the NCF-1 wildtype gene, as was the case for our patient. The second allele of the NCF-1 gene was affected by the frequent c.75.76delGT mutation that stems from a recombination of the NCF-1 wildtype gene with one of its pseudogenes. In conclusion, patients with NCF-1-deficient CGD may also harbour microdeletions that result in WBS or other hereditary disorders; therefore, it is important to perform a thorough genetic analysis in order to initiate appropriate therapy for these patients.